Diurnal and seasonal variations of the incoming solar radiation flux at a tropical station, Ile-Ife, Nigeria. Issue 5 (May 2019) - Soneye, Olanrewaju Olukemi; Ayoola, Muritala Ajayi; Ajao, Iyiola Adewale; Jegede, Oluwagbemiga Olawale
Abstract: The diurnal and seasonal variations of the incoming solar radiation have been studied by analysing two years data measured between January, 2016 to December, 2017 at a Tropical station, Ile-Ife (7.53°N; 4.54°E), Nigeria. The maximum incoming solar radiation flux which occurs between 13:00 – 14:00 LT and varies in the course of the year from 639.5 ± 171.6 Wm -2 (with large fluctuations) in the wet months (March – October) to 700.7 ± 105.2 Wm -2 in the dry months (November – February). The large differences in the values, diurnal and seasonal variation of the measured incoming solar radiation between the dry and wet seasons are attributed to the attenuation of the flux by aerosol particles in the dry season and increased cloudiness and humidity in the wet season. The monthly maximum values of 760.3 Wm -2 and 732.8 Wm -2 indicated a double peak from March to May and October to November respectively while a minimum of about 492.7 Wm -2 was recorded from July to August. Similarly, the daytime average had a double peak of 412.5 Wm -2 and 361.3 Wm -2 in March/April/May and October/November respectively, equally a minimum value of about 249.8 Wm -2 was recorded in July/August. The maximum value of the air temperature (which occurs around 15:00 LT) was observed to lag behind the maximum value of the incoming solar radiation (which occurs around 13:00 LT) by 2 hours at the study site. The statistical analysis of the monthly daytime averages of the incoming solar radiation showed that the intensity of the flux received at Ile-Ife (a tropical location) is high (about 67% of the incoming solar radiation are between the interval 325 and 400 Wm -2 ) throughout the year.